PENDUGAAN UMUR SIMPAN BUBUK JAHE MERAH - Sugiarto, Indah Yuliasih dan Tedy (Department of Agroindustrial Technology, Bogor Agricultural University, 2007)
ABSTRACTRed ginger is one kind of gingers, which is usually used for modern and traditional herb medicine. Fresh red ginger is easily damage; therefore preservation technology is needed. Red ginger is preserved by drying or being fermented as pickle. Red ginger powder is another preservation method that has advantages ie. easy to transport, store and use. Red ginger powder is the main product used for base or supplement material in drug industry. Furthermore it is not only consumed in powder form but also being extracted to yield an oleoresin and essential oil. During the storage period, the quality of red ginger powder can decrease; therefore shelf life dating of red ginger powder is needed.Based on decreasing of its color (chroma), red ginger powder without filler has the longest shelf life. The shelf life of red ginger powder without filler are 629 days (32.8 months of shelf life) at 25 oC, 544 days (18.1 months) at 30 oC, and 343 days(11.4 months) at 40 oC. Red ginger powder’s shelf life will decrease because of sucrose or dextrose monohydrate addition.Keywords : ginger powder, shelf life, lightness